Computer Aided Document Indexing for Accessing Legislation - Dalbelo Bašić, Bojana; Moens, Marie-Francine; Tadić, Marko (2008)
The paper gives the very first presentation of a joint Flemish-Croatian project CADIAL, its partners, aims, system and first results that are achieved. The overall aim of the project is to develop a system for automatic document indexing and retrieval of official documentation of the Republic of Croatia. Documents indexed with this system using Eurovoc thesaurus, will allow multilingual access and exploration of legislation to all Croatian and EU citizens. This approach represents a step forward in a wider context of dealing with legislative documentation in the digital age.
Projekt MZOS
Projekt MZOS
ENG